Hinduism and TESOL: Learning, Teaching and Student‐Teacher Relationships Revisited. Issue 2 (21st February 2013) - Sharma, Bal Krishna
Abstract This historical and philosophical survey provides an overview of 'learning''teaching' and 'student‐teacher relationships' as espoused in Hindu philosophy and its ancient educational practices. It shows that some of what have been regarded as the standard practices and innovations in language pedagogy in the Western world today, especially in Anglo‐American educational contexts, were in existence in the traditional Hindu educational ethos found in the Vedic and Upanishadic periods in the South Asian sub‐continent. This calls into question the representation of learner‐centeredness, autonomy and class discussions as innovative constructs. It shows that such practices in TESOL, for example, are not inherently West‐based and, thus, by contrast are in fact appropriate in non‐Western cultural contexts like Nepal.